The Relationship Between Cognitive Function Status and Quality of Life in High Risk Elderly at Uptd Social Service Center Griya Elderly Social Service of West Java Province - Alya Syafira, Wanda; Fazriana, Erlina; Komalaningsih, Sri (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2023)
High-risk elderly are elderly who reach age (> 70 years). As you get older, the status of cognitive function decreases and also the quality of life. Good, bad status of cognitive function can be seen from the aspects of orientation, language, attention, memory, function construction, calculation, and reasoning. Cognitive function will potentially affect the quality of life in terms of physical, psychological, social and environmental indicators. The purpose of this study was to determine the relationship between cognitive function status and quality of life in high-risk elderly at the Regional Technical Implementation Unit (UPTD) Griya Elderly Social Service Center, West Java Province Social Service. The design of this study uses the correlational method. Data collection tools used the Mini Mental Status Exam (MMSE) questionnaire and the World Health Organization Quality of Life version of Bref (WHOQoL-BREF). Univariate and bivariate data analysis, Spearman’s rho to see the relationship between variables. The results showed that most of the respondents (54%) had good global cognitive function status. And most of the quality of life on physical indicators (74%) is good, psychology (76%) is good, social (76%) is good, environment (78%) is good. There is a Relationship between Cognitive Functional Status and Quality of Life in High Risk Elderly in the Regional Technical Implementation Unit (UPTD) Griya Elderly Social Service Center, West Java Province Social Service. With a correlation value of 4 domains at age> 70 years. Physical (0.000), psychological (0.001), social (0.000), environmental (0.003). Conclusions and suggestions in this study, cognitive function will have the potential for quality of life problems thus respondents need to maintain routine guidance activities facilitated by the orphanage, both physical, mental spiritual, psychosocial, skills, arts and recreation guidance so that cognitive function remains good to quality his life is good.